2008
DOI: 10.1128/jvi.00074-08
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Group 1 Coronavirus Spike Proteins: How Furin Cleavage Is Traded Off against Heparan Sulfate Binding upon Cell Culture Adaptation

Abstract: A longstanding enigmatic feature of the group 1 coronaviruses is the uncleaved phenotype of their spike protein, an exceptional property among class I fusion proteins. Here, however, we show that some group 1 coronavirus spike proteins carry a furin enzyme recognition motif and can actually be cleaved, as demonstrated for a feline coronavirus. Interestingly, this feature can be lost during cell culture adaptation by a single mutation in the cleavage motif; this, however, preserves a heparan sulfate binding mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 49 publications
4
110
0
Order By: Relevance
“…This stretch had been also observed in the sequence of the S protein of Elmo/02 (position 801-805), but in this strain an Ala residue has replaced Val at position 803 (Pratelli et al, 2003). With few exceptions (de Haan et al, 2008), other alphacoronaviruses do not share this finding. The E protein is 82-aa long and does not present any Nglycosylation sites, whereas three N-glycosylated residues have been detected in the 264-aa long M protein, which is in agreement with what has been observed in other FCoV/CCoV strains, with the exception of CCoV-II isolate BGF10 that shows only two glycosylated Asn residues.…”
Section: Ccov-i Genomic Organizationmentioning
confidence: 50%
“…This stretch had been also observed in the sequence of the S protein of Elmo/02 (position 801-805), but in this strain an Ala residue has replaced Val at position 803 (Pratelli et al, 2003). With few exceptions (de Haan et al, 2008), other alphacoronaviruses do not share this finding. The E protein is 82-aa long and does not present any Nglycosylation sites, whereas three N-glycosylated residues have been detected in the 264-aa long M protein, which is in agreement with what has been observed in other FCoV/CCoV strains, with the exception of CCoV-II isolate BGF10 that shows only two glycosylated Asn residues.…”
Section: Ccov-i Genomic Organizationmentioning
confidence: 50%
“…For example, type II FCoV S protein binds to the virus receptor, aminopeptidase N (APN), but type I FCoV S protein does not bind to APN (Hohdatsu et al, 1998). In addition, type I FCoV S protein binds to heparin, but type II FCoV S protein does not (de Haan et al, 2008). The differences in these S protein properties between the serotypes may also influence the differences in the effects of U18666A.…”
Section: Discussionmentioning
confidence: 99%
“…According to , subsequent escape from endosomes is mediated by cathepsin B for FIPV strains 79-1146 and DF2, while for the enteric strain 79-1683 low pH in endocytic compartments and cathepsin L need to assist cathepsin B. In contrast, de Haan et al (2008) observed that infection with FIPV 79-1146 appears to be insensitive to cathepsin inhibitors.…”
Section: Introductionmentioning
confidence: 99%